Hydrazine modified g-C3N4 with enhanced photocatalytic activity for degradation of indigo carmine. (1st November 2022) - Valencia G, Karen; Hernández-Gordillo, Agileo; Méndez-Galván, Melissa; Morett, Diego; Rodil, Sandra E.
Abstract: Polymeric graphitic carbon nitride (g-C3 N4 ) was obtained from urea and modified by heat polymerization at 550 °C in the presence of hydrazine as a modifier agent. The influence of in-situ generated NH3 by hydrazine decomposition at different contents (0.5, 1, 1.5, and 2 mL) on the physicochemical properties and surface properties (water contact angle and point of zero charge) of the g-C3 N4 were investigated. The modified g-C3 N4 were analyzed by X-ray diffraction, scanning electron microscopy, diffuse reflectance spectroscopy, X-ray photoelectron spectroscopy, photoluminescence, Fourier Transform Infrared, water contact angle, surface area, and the point of zero charge. The in-situ generated NH3 induced an evolution from nano-flakes to lamellar plate morphology depending on stacked interplanar. The influence of surface properties on the photocatalytic response of the unmodified and modified g-C3 N4 was tested in the photodegradation of indigo carmine dye at pH = 3.5 and 6.5 solutions under blue LEDs light. The photostability of the samples was tested after 4 cycles of reaction. The properties (surface area (SA); water contact angle (WCA), and optical gap) influence the photocatalytic response, which was summarized in a single parameter defined as SA/(WCA*gap). The maximum value of this product match with results obtained for the most active photocatalyst (U-Hz1). Graphical abstract: Image 1 Highlights: The modified g-C3 N4 were prepared by heat polymerization in the presence of hydrazine. PZC and the water contact angle of g-C3 N4 varies as function of generated NH3 contents. The optical absorption of g-C3 N4 towards visible light was achieved by N vacancies. The modified g-C3 N4 exhibited high apparent kinetic rate constant for IC degradation.